Analisis Permintaan Kopi Bubuk di Kota Denpasar - WIJAYANTI, NI NYOMAN FITRIA ERA; SUDARMA, I MADE; DEWI, IDA AYU LISTIA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2023)
Demand Analysis of Ground Coffee in Denpasar City. Demand for ground coffee in Denpasar is uncertain because there is no definite data that can describe the level of public consumption of ground coffee. People's tastes are very relative and are changing over time. Consumers in buying a product will often buy more at a low price and will reduce purchases of a product at a high price and switch to substitute goods for that good. The purpose of this study is to analyze the affectdemand factors for ground coffee in Denpasar City and the effect of changes in ground coffee prices, prices of other goods and income on changes in ground coffee demand in Denpasar City. The data used is quantitative data obtained from secondary and primary data sources. Methods of data collection is done by the method of questionnaires and literature study. This study used a purposive sampling technique of 100 samples which were then analyzed using multiple linear regression analysis with the Cobb-Douglas model. The independent variables in this study are the price of ground coffee (X1), the price of tea (X2), the price of instant coffee (X3), the price of granulated sugar (X4), income (X5), and the number of family members (X6). The function of the model is lnY= 2.066 ¬ 0.561 lnX1** + 0.852 lnX2** + 0.123 lnX3 ¬ 0.463 lnX4 + 0.171 lnX5* + 0.624 lnX6**. Factors that affectdemand for ground coffee in Denpasar City are the price of ground coffee, the price of tea and the number of family members. Variables of instant coffee prices, sugar prices and income have no effect on the demand for ground coffee in Denpasar City. The price elasticity of ground coffee is inelastic. Tea and instant coffee are substitutes for ground coffee, while granulated sugar is complementary to ground coffee.